Combination of Hybrid Cryptography In One Time Pad (OTP) Algorithm And Keyed-Hash Message Authentication Code (HMAC) In Securing The Whatsapp Communication Application - Fanny Ramadhani; Umaya Ramadhani; Lutfi Basit (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2020)
Whatsapp is a cross-platform messaging application that allows us to exchange messages without SMS fees, because WhatsApp uses the same internet data package for email, web browsing, and more. The WhatsApp application reportedly has improved the security system of applications that are end to end encryption (E2EE). This proves that the WhatsApp manager paid considerable attention to privacy and security issues for its users. In addition, it also implies an important matter where business actors have begun to realize that the application of cryptographic services is part of a very promising business strategy or even determines the present and future consequences. The consequence of implementing E2EE is the description encryption process that takes place at the application layer (OSI layer). Cryptography is a study that studies methods to send messages in secret (that is, encrypted or disguised) so that only the intended recipient of the message can decode and read the message. For this reason, cirptography is one method that can implement E2EE on whatsapp. One Time Pad (OTP) is a type of symmetry algorithm, each key is only used for one message. If the key is random (cannot be reproduced) and only used once, then the algorithm is perfectly safe. The MAC (Message Authentication Code) is an identifier to prove the authenticity of a document obtained by using meaningless messages obtained from processing some of the contents of the document using a private key.